2015
DOI: 10.1097/hjh.0000000000000638
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of the association of ambulatory blood pressure characteristics with incident chronic kidney disease

Abstract: Loss of nocturnal blood pressure dipping, but not morning blood pressure surge, may promote the decline in GFR and increase the risk for development of CKD in high-risk individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Nonetheless, it is considerably greater than all other published investigations on the prognostic value of ABPM for predicting CKD risk. [36][37][38] Second, the reported findings, showing a highly significant relationship between risk for CKD and elevated sleep-time BP plus attenuated sleep-time relative BP decline, require validation and extrapolation to other ethnic groups. Our study also has several strengths, mainly being the first to provide results that are on the basis of systematic periodic multiple evaluations by ABPM throughout the median of 5.9 years of follow-up.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nonetheless, it is considerably greater than all other published investigations on the prognostic value of ABPM for predicting CKD risk. [36][37][38] Second, the reported findings, showing a highly significant relationship between risk for CKD and elevated sleep-time BP plus attenuated sleep-time relative BP decline, require validation and extrapolation to other ethnic groups. Our study also has several strengths, mainly being the first to provide results that are on the basis of systematic periodic multiple evaluations by ABPM throughout the median of 5.9 years of follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Kanno et al, 37 who evaluated 843 Japanese individuals by 24-hour ABPM only once on recruitment, concluded after a median follow-up of 8.3 years that nighttime BP was significantly associated with risk of CKD (defined as reduced eGFR or proteinuria) and a composite outcome of CKD and all-cause mortality, whereas the 24-hour and daytime ABP means as well as conventional clinic BP measurements were not; the sleep-time relative BP decline and the standard arbitrary nondipping classification did not significantly differ in relation to CKD risk. More recently, McMullan et al 38 conducted a prospective cohort study of 603 blacks without CKD defined on the basis of eGFR alone who underwent a unique 24-hour ABPM evaluation at baseline. After a median of 8.1 years of follow-up, the sleep-time relative SBP decline was the most significant predictor of incident CKD defined on the basis of a single and thus, unconfirmed reduced eGFR determined at the last of just two clinical assessments per participant performed during follow-up; moreover, a greater asleep but not awake BP mean was significantly associated with increased risk of CKD after adjusting for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of sleep-trough MBPS with deterioration of kidney function and development of CKD was observed in hypertensive [ 37 ] and normotensive subjects [ 32 ] previously, although in a population-based observational study this association was not reported to be significant among African Americans. [ 38 ] This heterogeneity in results may be due to the racial differences. Barbieri et al [ 39 ] showed sleep-trough MBPS is positively associated with microalbuminuria in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Over-activity of sympathetic neurons is considered to lead to renal damage via direct and indirect mechanisms, such as nitric oxide and catecholamine metabolism [30]. Furthermore, the Jackson Heart Study and Nurses’ Health study showed that decreased nocturnal BP fall and short sleep duration are associated with a decline in renal function [7, 8]. Inconsistent with previous reports, we found in the present study that nocturnal BP fall and sleep function including sleep duration were not significantly associated with incidence of CKD.…”
Section: Discussionmentioning
confidence: 99%